ABCA1 is direct target gene of miR-144-3p in chondrocyte - Bich Phuong, Ho Thi; Dang Quan, Nguyen; Kim Tram, Phan Thi; Nam Anh, Tang Ha; Truc Linh, Le Thi (Vietnam Journal of Biotechnology, 2023)
MicroRNA144-3p was reported to associate with osteoarthritis (OA) since it was upregulated in this disease. ABCA1 was also found to involve in OA. Bioinformatics algorithms showed ABCA1 was potential targets of miR-144-3p. This study aims to prove ABCA1 is direct targets of miR-144-3p experimentally. Expression of ABCA1 was determined by Realtime RT-PCR after performing the gain- and loss- function of miR-144-3p in chondrocyte. The 3’UTR containing several binding sites of miR-144-3p was subcloning. The vector with binding sites of miR-144-3p mutated was aslo created. Luciferase assay was performed to check the ability of miR-144-3p binding to ABCA1. Realtime RT-PCR showed that the overexpression of miR-144-3p inhibited ABCA1 expression. The Luciferase assay showed that miR-144-3p directly interacted with ABCA1 through its binding sites on the 3’UTR. These data suggested that ABCA1 is the direct target of miR-144-3p.